Valuing futures and options on volatility - Grünbichler, Andreas; Longstaff, Francis A. (Journal of Banking & Finance, 1996)
This paper presents simple closed-form expressions for volatility futures and option prices and examines their implications for the characteristics of these securities. We show that the properties of these volatility derivatives are fundamentally different from those of conventional option and futures contracts. This analysis also provides insights into the role that volatility derivatives may play in managing and hedging volatility risk in financial markets.